2016
DOI: 10.1080/02670836.2015.1137683
|View full text |Cite
|
Sign up to set email alerts
|

Hardness and wear behaviour of electroless Ni–B coatings

Abstract: Depth-dependent hardness variation of dimethylamine borane-reduced electroless Ni–5 wt-%B deposits has been examined using the nanoindentation technique. The deposits were characterised using ICP-OES, FESEM, XRD and DSC for evaluating the composition, morphology, structure and phase transformation behaviour, respectively. Coatings were also analysed for hardness and wear resistance. The surface of the as-plated deposit exhibits a typical nodular morphology. DSC traces show the presence of a single exothermic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 31 publications
(76 reference statements)
8
22
0
Order By: Relevance
“…This could be an indication of higher thermal stability of the deposits [29,39]. High microhardness of heat treated Ni-B and its ternary variants are in accordance with the literature [23][24][25][26][27][28][29].…”
Section: Microhardness Of Nickel Boron and Its Variantssupporting
confidence: 89%
See 3 more Smart Citations
“…This could be an indication of higher thermal stability of the deposits [29,39]. High microhardness of heat treated Ni-B and its ternary variants are in accordance with the literature [23][24][25][26][27][28][29].…”
Section: Microhardness Of Nickel Boron and Its Variantssupporting
confidence: 89%
“…Similar results have also been obtained for Ni-B-Mo coatings heat treated at 350 • C, as can be seen in Figure 2. Although, stable Ni 3 B phases are observed along with Ni (111) on heat treating Ni-B-Mo coating at 450 • C for 1 h. Precipitation of hard boride phases on heat treating Ni-B and its variants has been also reported in the literatures [23][24][25][26][27][28][29].The analysis of XRD results is presented in Table 3. The procedure for calculation of absolute integrated intensity of peaks and crystallite size is mentioned elsewhere [13,40].…”
Section: Composition Structure and Surface Morphology Of Nickel Bormentioning
confidence: 73%
See 2 more Smart Citations
“…The typical cauliflower like surface morphology and columnar growths further aid to the improvement of tribological properties by imparting self-lubricating properties and reducing the actual area of contact. [23][24][25] The wear mechanism and endurance life of Ni-B coatings has been studied extensively by Madah et al 26 Adhesive, abrasive, fatigue, and oxidational wear of the coatings were observed depending on the applied normal load and sliding distance. Phase transformations during the sliding wear process have a significant effect on wear behavior of Ni-B coatings as well as supporting the tribochemical patches.…”
Section: Introductionmentioning
confidence: 99%